Evaluating Chemical Stability Challenges in Surfactant Eor for High-Temperature, High-Salinity Reservoir: the Volve Field - Hamidah, Ghoty; Novia Rita; Purnamawati, Neneng (UIR PRESS, 2026)
This study evaluates the influence of surfactant concentration on oil recovery performance under high-temperature and high-salinity reservoir conditions in the volve field using numerical simulations. Several surfactant concentration scenarios were applied to analyze production response and recovery factor behavior. The result indicate that increasing surfactant concentration only slightly improves oil recovery, with recovery factor remaining within a narrow range from 19.82% to 19.93% across all scenarios. Limited performance is associated with thermal degradation, adsorption, salinity effects, and reduced interfacial tension efficiency under harsh reservoir conditions. This study is limited to numerical simulation and requires laboratory validation to confirm surfactant chemical behavior under actual reservoir conditions. Therefore, future research should prioritize laboratory evaluation of thermally stable surfactants before filed scale implementation.